2006
DOI: 10.1007/s00787-006-0534-7
|View full text |Cite
|
Sign up to set email alerts
|

Emotional and behavioural difficulties in children of parents with multiple sclerosis

Abstract: Emotional and behavioural problems were investigated in children who have a parent with multiple sclerosis (MS), in relation to factors such as family dysfunction, parental depression and illness-related characteristics. The participants were 56 MS patients, their spouses and one randomly selected child aged 4-17 years, and a comparison group of 64 children and both their parents, none of whom reported somatic illness. Emotional and behavioural problems in the children were identified by reporting of both pare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
74
1
9

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(93 citation statements)
references
References 17 publications
9
74
1
9
Order By: Relevance
“…33 Studies have reported a greater risk of depression, anxiety, somatization, difficulty in relating to others and greater emotional and behavioral problems in children of MS parents. 6,7,[34][35][36] It is possible that children of MS parents have relatively normal developmental trajectories in early childhood, but that the stress of parental MS manifests with vulnerability on the physical health dimension first. 37 Our study was restricted to early childhood development and we cannot rule out effects in later childhood and adolescence.…”
Section: Discussionmentioning
confidence: 99%
“…33 Studies have reported a greater risk of depression, anxiety, somatization, difficulty in relating to others and greater emotional and behavioral problems in children of MS parents. 6,7,[34][35][36] It is possible that children of MS parents have relatively normal developmental trajectories in early childhood, but that the stress of parental MS manifests with vulnerability on the physical health dimension first. 37 Our study was restricted to early childhood development and we cannot rule out effects in later childhood and adolescence.…”
Section: Discussionmentioning
confidence: 99%
“…Die niederländische Forschergruppe um Visser Huizinga et al, 2005) (Watson et al, 2006). In der griechischen COSIP-Studie an 56 Familien mit einem an Multipler Sklerose erkrankten Elternteil zeigte sich, dass internalisierende Symptome der Kinder signifikant mit den Depressionswerten der Mütter korrelierten, unabhängig davon, ob diese selbst oder die Väter in den Familien erkrankt waren (Diareme et al, 2006). In der bereits erwähnten multiperspektivisch angelegten transnationalen Untersuchung von 144 Familien aus drei Ländern mit einem an Multipler Sklerose erkrankten Elternteil korrelierte die Depressivität kranker Mütter und noch deutlicher die des gesunden Elternteils mit internalisierenden Auffälligkeiten der Kinder.…”
Section: Assoziierte Risiko-und Schutzfaktorenunclassified
“…Dette behovet står i motsetning til foreldres umiddelbare tanke om at de vil skåne barna for vanskelig og bekymringsfull informasjon (9,10). Videre bør barn og unge få støtte til å takle egen hverdag ved å laere gode mestringsstrategier (5,11).…”
Section: Konsekvenserunclassified